Work Satisfaction and Leadership Styles in Public and Private Education Institutions in Chile - chiang vega, maria margarita; Gómez Fuentealba, Nelly M.; Salazar Botello, Carlos M. (Cuadernos de Administración, 2014)
The aim of this research was to analyze the relationship between work satisfaction and leadership style in 145 faculty staff in public and private education institutions in Chile. To measure work satisfaction, the questionnaire by Chiang et al., (2008) was used and for leadership styles, a questionnaire was used based on the situational theory by Hersey and Blanchard (Chiang and Salazar 2011). The reliability of the scales is variable and in all cases adequate, with Cronbach’s alpha between 0.7 and 0.9. Values of work satisfaction are around 4 (scale from 1 to 5), placing those surveyed at a level as “satisfied with their work”. No results are available to indicate low levels of satisfaction. Values regarding instruction, persuasive, participation, and delegation leadership styles range between 3 and 3.5, both for the female and male samples. The results indicate that the four leadership styles are present with medium levels. Statistically significant correlations exist, in low levels, among instruction, persuasion, and participation leadership styles with all the factors of work satisfaction. Positive correlations are highlighted between satisfaction with the way their work is carried out and the persuasion and participation leadership styles. The delegation leadership style does not correlate with any of the factors associated to work satisfaction